Population confidence in the health system in 15 countries: results from the first round of the People's Voice Survey - Margaret E Kruk, ProfMD; Neena R Kapoor, MSc; Todd P Lewis, PhD; Catherine Arsenault, PhD; Eleni C Boutsikari, MSc; João Breda, PhD; Susanne Carai, MD; Kevin Croke, PhD; Rashmi Dayalu, MPH; Günther Fink, PhD; Patricia J Garcia; Munir Kassa, MD; et al. (Elsevier, 2024)
Summary: Population confidence is essential to a well functioning health system. Using data from the People's Voice Survey-a novel population survey conducted in 15 low-income, middle-income, and high-income countries-we report health system confidence among the general population and analyse its associated factors. Across the 15 countries, fewer than half of respondents were health secure and reported being somewhat or very confident that they could get and afford good-quality care if very sick. Only a quarter of respondents endorsed their current health system, deeming it to work well with no need for major reform. The lowest support was in Peru, the UK, and Greece-countries experiencing substantial health system challenges. Wealthy, more educated, young, and female respondents were less likely to endorse the health system in many countries, portending future challenges for maintaining social solidarity for publicly financed health systems. In pooled analyses, the perceived quality of the public health system and government responsiveness to public input were strongly associated with all confidence measures. These results provide a post-COVID-19 pandemic baseline of public confidence in the health system. The survey should be repeated regularly to inform policy and improve health system accountability.